Kidney tissue proteome profiles in short versus long duration of delayed graft function – a pilot study in donation after circulatory death donors - Lo Faro, ML; Rozenberg, K; Huang, H; Maslau, S; Bonham, S; Fischer, R; Kessler, B; Leuvenink, H; Sharples, E; Lindeman, JH; Ploeg, R (Elsevier, 2024)
Introduction: Delayed graft function (DGF) is often defined as the need for dialysis treatment in the first week after a kidney transplantation. This definition, though readily applicable, is generic and unable to distinguish between “types” of DGF or time needed to recover function that may also significantly affect longer-term outcomes. We aimed to profile biological pathways in donation after circulatory death (DCD) kidney donors that correlate with DGF and different DGF durations. Methods: A total of N = 30 DCD kidney biopsies were selected from the UK Quality in Organ Donation (QUOD) biobank and stratified according to DGF duration (immediate function, IF n = 10; “short-DGF” (1–6 days), SDGF n = 10; “long-DGF” (7–22 days), LDGF n = 10). Samples were matched for donor and recipient demographics and analyzed by label-free quantitative (LFQ) proteomics, yielding identification of N = 3378 proteins. Results: Ingenuity pathway analysis (IPA) on differentially abundant proteins showed that SDGF kidneys presented upregulation of stress response pathways, whereas LDGF presented impaired response to stress, compared to IF. LDGF showed extensive metabolic deficits compared to IF and SDGF. Conclusion: DCD kidneys requiring dialysis only in the first week posttransplant present acute cellular injury at donation, alongside repair pathways upregulation. In contrast, DCD kidneys requiring prolonged dialysis beyond 7 days present minimal metabolic and antioxidant responses, suggesting that current DGF definitions might not be adequate in distinguishing different patterns of injury in donor kidneys contributing to DGF.